An update on the management of hepatitis C virus-related arthritis. (October 2014) - Palazzi, Carlo; D'Amico, Emilio; D'Angelo, Salvatore; Gilio, Michele; Leccese, Pietro; Olivieri, Ignazio
<x xml:space="preserve">Abstract</x> Introduction: Hepatitis C virus (HCV)-related arthritis is an uncommon disease belonging to the autoimmune disorders due to the chronic stimulus exerted by the virus on the immune system. It shows two clinical subsets: a symmetrical polyarthritis resembling rheumatoid arthritis but less aggressive and an intermittent mono-oligoarthritis involving the lower limbs. Areas covered: We extensively review the current literature using the largest electronic databases (MEDLINE, EMBASE and COCHRANE) with regard to HCV-related arthritis (HCVrA) and studies focusing on the co-existence of HCV and other kinds of arthritides. Expert opinion: The therapeutic approach to HCVrA remains largely empirical, because few studies have been published on this topic. Mainstream treatment based on the administration of hydroxychloroquine and low doses of corticosteroid is still largely preferred. Cyclosporine represents a useful alternative due to its antiviral properties. Anti-TNF agents are safe, but their hypothetic use appears excessive for a mild disorder such as HCVrA. IFN-α (and more recently pegylated IFN-α) when administered as a component of the combined (IFN-α + ribavirin) anti-HCV therapy can promote the appearance or the worsening of several autoimmune HCV-related disorders, including arthritis. New and forthcoming antiviral molecules will be used in the near future for a revolutionary IFN-free treatment.